Physical fitness of non-disabled school-aged children born with extremely low birth weights. (January 2019) - Tamai, Kei; Nishihara, Masahiro; Hirata, Katsuya; Shiraishi, Jun; Hirano, Shinya; Fujimura, Masanori; Yano, Suguru; Kanazawa, Tadahiro; Kitajima, Hiroyuki
Abstract: Background: The assessment of long-term outcomes in survivors born with extremely low birth weights (ELBWs) has become increasingly important. However, little has been reported on the physical fitness of non-disabled school-aged children born with ELBWs. Aims: To assess the physical fitness of non-disabled school-aged children born with ELBWs. Study design: Retrospective cohort study. Subjects: We analyzed 169 ELBW infants without cerebral palsy or intellectual disability (based on the Wechsler Intelligence Scale for Children—Third Edition (WISC-III) Full Scale intelligence quotient (IQ) test < 70). Outcome measures: Physical fitness was assessed using the grip strength, sit-up repetitions, sit & reach, side steps, standing long jump, and softball throw tests. T-scores were calculated using national survey data. Results: The T-scores for the grip strength, sit-up repetitions, sit & reach, side steps, standing long jump, softball throw tests, and the overall T-score were 43.7 ± 7.5, 44.2 ± 10.5, 46.0 ± 9.7, 40.9 ± 8.0, 40.0 ± 9.8, 42.4 ± 8.1, and 42.9 ± 5.5, respectively. After adjusting for other age-related factors, the height (SD score), WISC-III Performance IQ score, and percent predicted forced vital capacity (FVC) independently predicted the overall T-scores. Their standardized partial regression coefficients (β) were 0.334 ( p = 0.009), 0.190 ( p = 0.022), and 0.187 ( p = 0.032), respectively. Conclusions: Our cohort's physical fitness at approximately 8 years of age was significantly impaired compared to average Japanese children of the same age. Height, FVC, and Performance IQ independently predicted physical fitness, with height being the strongest predictor. Highlights: We investigated physical fitness of non-disabled school-aged children born with ELBW. Our cohort's physical fitness was significantly impaired compared to average Japanese children of the same age. Height, FVC, and Performance IQ independently predicted physical fitness, with height being the strongest predictor.